2013
DOI: 10.1002/erv.2263
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amenorrhea in Anorexia Nervosa: Impact on Characteristic Masculine and Feminine Traits

Abstract: Animal studies indicate gonadal hormones at puberty have an effect on the development of masculine and feminine traits. However, it is unknown whether similar processes occur in humans. We examined whether women with anorexia nervosa (AN), who often experience primary amenorrhea, exhibit attenuated feminization in their psychological characteristics in adulthood due to the decrease/absence of gonadal hormones at puberty. Women with AN were compared on a number of psychological characteristics using General Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Hence, it is unclear whether alterations in smell are related to starvation or malnutrition. The role of metabolic hormones in the sensory and regulatory aspects of energy homeostasis has been described in the literature [48,49]. Accordingly, the interaction between olfaction, gut hormones and eating behavior has also been described in the literature regarding metabolic disorders (such as obesity and anorexia nervosa) [23].…”
Section: Discussionmentioning
confidence: 98%
“…Hence, it is unclear whether alterations in smell are related to starvation or malnutrition. The role of metabolic hormones in the sensory and regulatory aspects of energy homeostasis has been described in the literature [48,49]. Accordingly, the interaction between olfaction, gut hormones and eating behavior has also been described in the literature regarding metabolic disorders (such as obesity and anorexia nervosa) [23].…”
Section: Discussionmentioning
confidence: 98%
“…Lesser body fat and high calorie restriction diets are one of the major reasons behind why women with anorexia nervosa develop primary amenorrhea. It was suspected that these changes in the hormones could be responsible for bringing about any feminine and masculine characteristics in these women too (J. H. Baker et al, 2014). A relationship between presence of menstrual irregularities and high possibilities of developing momentary stress and episodes of skipping meals was also found in women with anorexia nervosa and this showed that menstrual irregularities can have an effect on eating behaviours and even perceived stress in the long run (J. H. Baker et al, 2014) .…”
Section: Anthropometrymentioning
confidence: 99%